Studies on the active constituents and the related mechanisms of Jinhong Tablet in the treatment of chronic gastritis based on network pharmacology and in vivo experimental validation - Zhihui Liu; Mengwen Shang; Zhenzhong Wang; Xu Li; Wei Xiao; Jun Yin (Elsevier, 2023)
Objective: Chronic gastritis (CG), the common disease in the digestion department at present, is a chronic inflammation of gastric mucosa. In the absence of an effective prevention and treatment, chronic inflammation of the stomach can lead to gastric cancer. Jinhong tablet (JHT), originated from "Jinlingzi San" in the Yuan Dynasty of Chinese history (1271 AD-1368AD), is one of the most effective medicines used to treat CG in clinical practice with the effects of dispersing stagnated liver qi to relieve depression and promoting blood circulation and relieving pain. However, the active ingredients and mechanisms of JHT in the treatment of CG have not been clarified. Therefore, this study aimed to elucidate the active constituents and mechanisms based on network pharmacology. Methods: First of all, the chemical components of JHT were identified using an UPLC-QTOF-MS, and then the obtained components were used to establish the active and potential ingredient-target networks. A protein-protein interaction (PPI) network was then constructed, and reactome pathway enrichment analysis was performed to determine the key targets in the treatment on CG of JHT. In addition, the further pathway analysis of JHT against CG was carried out on the platform of Bio Informatics. In the end, the predicted targets were validated by ELISA. Results: A total of 98 chemical constituents were identified in JHT, and under the screening criteria of oral bioavailability (OB) ≥30% and drug-likeness (DL) ≥0.18, 27 active ingredients were determined. Further network pharmacology analysis revealed that quercetin, kaempferol, morin, naringenin and tetrahydroberberine are vital components for the anti-CG efficacy of JHT, and JUN, TP53, TNF, VEGFA and AKT1 with highest average scores were considered as the key central genes. Additionally, the subsequent validation studies confirmed JUN was a key target and the therapeutic effect of JHT for CG may be related to the decrease of inflammatory cytokine such as IL-1β and IL-8. Conclusion: In summary, our results indicate that JHT can treat CG by reducing the inflammatory cytokines directly or indirectly to play anti-inflammatory activity and flavonoids may be the key constituents.